Business intelligence : 6th European Summer School, eBISS 2016, Tours, France, July 3-8, 2016, Tutorial lectures /: 6th European Summer School, eBISS 2016, Tours, France, July 3-8, 2016, Tutorial lectures. (2017) - Unknown
No abstract available